Changes in Expectation of Relationship Permanence, Pregnancy Acceptability and Desire, and Contraceptive Use Over Time Among Young Latino/a Women and Men: An Exploratory Analysis - Arcara, Jennet (Contraception, 2020)
OBJECTIVE: We longitudinally assess associations between changes in expectation of relationship permanence—a measure that incorporates both relationship duration and commitment—pregnancy desire and acceptability, and highly effective contraception use among young U.S. Latino/as. STUDY DESIGN: We used multivariable logistic regression to analyze associations between changes in relationship factors, pregnancy acceptability and desire, and contraceptive method use over 6 months among 299 U.S. Latino/a women and men (ages 18-34) in relationships in a longitudinal study (retention rate: 32.4%). RESULTS: Respondents who found a pregnancy less acceptable at endline than at baseline were more likely to use highly effective contraception at endline (OR 2.97, 95% CI 1.09,8.08). Respondents estimating an increase in relationship permanence more than one standard deviation of the mean were 4.90 (95% CI 1.17,20.55) times more likely to use highly effective contraception at endline, compared to those without a change in estimation of relationship permanence. CONCLUSION: In this longitudinal study of young adult Latino/as in relationships, we found associations between changes in respondents’ perceptions of the acceptability of a pregnancy and expectation of the permanence of their relationship and highly effective contraceptive use. Our findings reiterate the complicated, intertwined links between relationship dynamics, pregnancy orientation, contraception, and time. IMPLICATIONS: The significance of decreased pregnancy acceptability (but not desire) for using highly effective contraception suggests the importance of acknowledging pregnancy acceptability in contraceptive counseling, particularly because providers are more likely to direct Latino/a young adults towards methods that may not fulfill their contraceptive desires. Including discussion of young people’s expectations of relationship permanence may also be meaningful in counseling.